Transition from LDL apheresis to evolocumab in heterozygous FH is equally effective in lowering LDL, without lowering HDL cholesterol. (August 2016) - Lappegård, Knut Tore; Enebakk, Terje; Thunhaug, Hilde; Hovland, Anders
Abstract: Background and aims: LDL apheresis is effective in reducing low-density lipoprotein (LDL) cholesterol (LDL-C) and clinical endpoints, however, the treatment is invasive and time consuming. In the present study, we explored lipid profiles and quality of life in patients with heterozygous familial hypercholesterolemia (FH) when altering the treatment regimen from weekly LDL apheresis to bi-weekly evolocumab treatment. Methods: Three patients with FH and coronary artery disease, established in LDL apheresis for 135 ± 13(SD) months, participated. The patients were examined with blood sampling before and after LDL apheresis (week 0), and before evolocumab administration (week 1–7), quality of life was assessed (week 1, 3, 7). Results: The historically highest, untreated LDL-C was 10.3 ± 0.8 mmol/L, during weekly LDL apheresis, 5.5 ± 0.9 mmol/L pre-apheresis and 1.2 ± 0.2 mmol/L post-apheresis ( p = 0.02). One week after apheresis, LDL-C was 6.1 ± 0.7 mmol/L, after three (bi-weekly) injections of evolocumab, LDL-C was 5.0 ± 0.7 ( p < 0.001). High-density lipoprotein cholesterol (HDL-C) was reduced from 1.0 ± 0.2 mmol/L pre- to 0.5 ± 0.1 mmol/L post-apheresis ( p = 0.03), it increased after apheresis and remained constant during evolocumab treatment. Lipoprotein(a) (Lp(a)) decreased from 484 ± 76 mg/L pre- to 142 ± 15 mg/L post-apheresis ( p = 0.02), but increased during evolocumab treatment, with a small increase from week one to week seven ( p < 0.01). There was a non-significant trend towards an increase in perceived health status (week 0; 57 ± 21, week three; 65 ± 9 and week seven; 77 ± 10). Conclusions: In the current study, we demonstrate reductions in LDL-C, HDL-C, triglycerides and Lp(a) during apheresis. Switching from LDL apheresis to evolocumab maintained the LDL-lowering effect but did not decrease HDL levels. Highlights: LDL apheresis is effective in reducing LDL cholesterol and Lp(a). HDL cholesterol is also reduced during LDL apheresis. Switching from LDL apheresis to PCSK9 inhibition maintain the LDL lowering effect. PCSK9 inhibition does not lower HDL cholesterol.